2005
DOI: 10.1109/tvlsi.2004.840763
|View full text |Cite
|
Sign up to set email alerts
|

A transaction-based unified architecture for simulation and emulation

Abstract: The availability of millions of transistors on a single chip has allowed the creation of complex on-chip systems. The functional verification of such systems has become a challenge. Simulation run times are increasing, and emulation is now a necessity. Creating separate verification environments for simulation and emulation slows the design cycle and it requires additional human efforts. This paper describes a layered architecture suitable for both simulation and emulation. The architecture uses transactions f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Functional verification of such systems has been problematic [11]. Nowadays, the constant increase in the complexity of designs has led to functional testing to run application specific integrated circuits [9].…”
Section: Emulatorsmentioning
confidence: 99%
“…Functional verification of such systems has been problematic [11]. Nowadays, the constant increase in the complexity of designs has led to functional testing to run application specific integrated circuits [9].…”
Section: Emulatorsmentioning
confidence: 99%
“…Research found that the speed bottleneck of this methodology is mostly caused by the ping-pong mode of data transmission between workstation software and the FPGA emulator, thus resulting in that channel transmission time takes too much proportion of total time [1] [2]. In order to overcome the emulation channel transmission limits between workstations and FPGA, solutions are given by published papers [3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the research concentrates on methodology partitioning a system into transaction-level test, transactors and design [2], transaction-level modeling [3], development environment in system level [4], scheme for reducing communication traffic [5] without investigation on transaction-based architecture, especially from viewpoint of hierarchy architecture from bottom level to top level.…”
Section: Introductionmentioning
confidence: 99%